PENGARUH TRANSFORMATIONAL LEADERSHIP DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI GLOBAL PRESTASI SCHOOL BEKASI MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Tambunan, Nelli; Sudibjo, Niko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers are not only required to have professional competence, but also to apply these competencies in performance supported by transformational leadership, organizational culture, and job satisfaction. This study aims to analyze the effect of transformational leadership and organizational culture on teacher performance at Global Prestasi School Bekasi through job satisfaction as a mediating variabel. The subjects of the study were a population of 62 teachers from elementary to high school levels at Global Prestasi School, Bekasi, with a quantitative approach through survey design. Data was collected using a standardized questionnaire and analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) method. The results of the study indicate that transformational leadership and organizational culture positively influence job satisfaction. Job satisfaction has been shown to have a significant direct effect on teacher performance. However, transformational leadership and organizational culture have not provided a significant direct effect on teacher performance, but rather through the mediation of job satisfaction. This study shows the importance of job satisfaction as a key factor in improving teacher performance. In addition, the results of this study provide important implications for school management, especially in strengthening transformational leadership and a supportive organizational culture. Thus, schools can create a conducive work environment to improve teacher satisfaction and performance.